Changes in consumer energy intensity in Malaysia - Abdullah Chik, Norlaila; Abdul Rahim, Khalid; Saari, Mohd Yusof; Alias, Emmy Farha (Faculty of Economics and Management, Universiti Putra Malaysia, 2012)
This paper proposes an IO-SDA model based on Hybrid input-output table, to identify the source of changes in the energy intensity, energy input and consumption level in the Malaysian household. This study is conducted in two stages: first, to identify the multiplier (energy intensities) by using the Hybrid input-output analysis, and second, to identify the sources of change in the Malaysian household energy consumption (energy and non-energy based products) for the periods 1991 to 2000, 2000 to 2005, and 1991 to 2005 by using IO-SDA model. The major finding of this study is that total household energy consumption has increased rapidly, mainly because of an increase in private consumption by household and increase in energy use in the production sector for consumer goods. From this finding, government and policy-makers should give more attention to energy consumption by promoting renewable energy resources to avoid shortage of energy supply in the future. Currently, the Malaysian economy is greatly dependent on non-renewable energy.